'Continuously innovating the study of continuous innovation: from actionable knowledge to universal theory in continuous innovation research'. (1st January 2012) - Martini, Antonella; Gastaldi, Luca; Magnusson, Mats; Laugen, Bjørge Timenes
Whereas there is a wealth of contributions on the topic of continuous innovation (CI) in firms, there is still a clear need for works addressing how the existing knowledge on combining various types of innovation with operational excellence and strategic flexibility in a fruitful manner. Any attempt to generate actionable knowledge about CI that at the same time lives up to the traditional academic requirements of rigor and relevance poses significant challenges to researchers, calling for a more comprehensive and multi-faceted methodological approach, attending to multiple evaluation criteria and possible revisions of research roles and processes. This paper aims to recommend how to produce CI actionable knowledge and to take the first steps in progressing from this form of knowledge to a universal theory of CI. In doing so, the paper calls for a 'continuous innovation' in the way CI research is accomplished, and aims at proposing some key building blocks and evaluation criteria of a basic framework able to overcome the pre-paradigmatic stage in which CI research seems to be stuck. Moreover, it presents four papers from the International CINet Conference held in 2007 Göteborg (SE) and one from the 2010 Zürich.